PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA PROMOSI PADA BISNIS PEMPEK LESTARI - Ahmad Alif Ikhsani; Dhanar Intan Surya Saputra (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2023)
Internet development is happening very rapidly, and the exchange of information is becoming easier and faster. It makes people tend to use the internet more to communicate and interact. Social media has many benefits in everyday life, and doing business is no exception. For businesses, social media can be used as a tool to promote a product or service. The purpose of the activity is to find out how to use social media as a promotional media for a product so that consumers can reach it, what obstacles exist when using social media for the promotion of a food product, and what solutions should be done in utilizing social media as a promotional media. The method in this activity uses analysis and mentoring approach. The results of the action show that there are several obstacles to the use of social media as promotional media. Through this activity, these obstacles can be faced and resolved by the use of social media as a promotional medium by Dapoer Lestari. The solution is to use social media, Facebook, to promote the Pempek Dapoer Lestari business. Key Words: Media Social, Promotions, Facebook